Early diastolic mitral annular velocity and color M-mode flow propagation velocity in the evaluation of left ventricular diastolic function in patients with Fabry disease - Palecek, Tomas; Linhart, Ales; Lubanda, Jean Claude; Magage, Sudheera; Karetova, Debora; Bultas, Jan; Aschermann, Michael (Heart and vessels, 2006)
Fabry disease is an X-linked genetic disorder characterized by progressive intracellular accumulation of neutral glycosphingolipids. Cardiac involvement is frequent and left ventricular (LV) diastolic dysfunction is present in most of the affected subjects. Pulsed-wave tissue Doppler echocardiography (PW-TDE) and color M-mode are new Doppler methods for LV diastolic function evaluation. Their role in the assessment of Fabry disease-related cardiomyopathy remains to be established. In this study we aimed to determine the utility of PW-TDE and color M-mode-derived parameters in the assessment of LV diastolic function in patients with Fabry disease. Eighty-one echocardiographic examinations performed in 35 patients affected by Fabry disease were retrospectively analyzed. Early diastolic lateral mitral annular velocity (E(m)) determined by PW-TDE and color M-mode flow propagation velocity (V(p)) were measured and compared to LV filling patterns obtained using standard Doppler indexes. The receiver operating characteristics (ROC) curves method was used to determine the summary measure of relative accuracy for E(m) and V(p). A comparison of ROC curves showed a significant difference for areas under the curve in favor of E(m) (P < 0.001). Pseudonormal filling pattern, higher LV mass index, higher relative wall thickness, larger left atrial diameter, and older age were more frequent (all P < 0.001) in patients with incorrect diagnosis of normal LV diastolic function based on the measurement of V(p). E(m) appears to be superior to V(p) in the assessment of LV diastolic function in patients with Fabry disease. V(p) fails to detect abnormal LV diastolic function in subjects with pronounced concentric LV remodeling and pseudonormal filling pattern.
Keywords: Fabryho nemoc; Stroke Volume; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; Heart Atria; Blood Flow Velocity; Retrospective Studies; počítačové zpracování obrazu; Middle Aged; Sensitivity and Specificity; plocha pod křivkou; mužské pohlaví; False Negative Reactions; funkce levé komory srdeční; Adult; Echocardiography, Doppler, Color; tepový objem; srdeční síně; Fabry Disease; hypertrofie levé komory srdeční; barevná dopplerovská echokardiografie; pulzní dopplerovská echokardiografie; ženské pohlaví; Ventricular Remodeling; retrospektivní studie; Humans; Echocardiography, Doppler, Pulsed; Hypertrophy, Left Ventricular; mitrální chlopeň; lidé středního věku; senzitivita a specificita; Image Processing, Computer-Assisted; Area Under Curve; falešně negativní reakce; remodelace komor; dospělí; Mitral Valve; rychlost toku krve; Female; výzkumný projekt; Research Design; lidé; Male; Ventricular Function, Left